2004
DOI: 10.1002/sia.1640
|View full text |Cite
|
Sign up to set email alerts
|

XPS depth profile analysis of non‐stoichiometric NiO films

Abstract: Antiferromagnetic NiO films used for pinning layers in spin valve systems were prepared by reactive sputtering from an NiO target with variation of the oxygen/argon mixture in the sputter gas. Using XPS depth profiling we investigated the NiO x overstoichiometry (x > 1) in the films that was found by other methods and the chemical changes in the films during annealing. A direct detection of Ni 3+ failed because of strong preferential sputtering with the formation of metallic Ni during sputtering. By means of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(152 citation statements)
references
References 22 publications
8
142
0
Order By: Relevance
“…39 In addition, a weak splitting peak of Ni 2p3/2 peak was also observable at ∼855.3 eV, which is due to the presence of oxidation state of Ni 3+ . 40,41 But the above XRD measurements show that no any other impurity phases were observed in all annealed samples within the detection limit of X-ray diffractometer. This indicated that there are only very few amount of Ni 43,44 or theoretical calculation.…”
Section: Resultsmentioning
confidence: 70%
“…39 In addition, a weak splitting peak of Ni 2p3/2 peak was also observable at ∼855.3 eV, which is due to the presence of oxidation state of Ni 3+ . 40,41 But the above XRD measurements show that no any other impurity phases were observed in all annealed samples within the detection limit of X-ray diffractometer. This indicated that there are only very few amount of Ni 43,44 or theoretical calculation.…”
Section: Resultsmentioning
confidence: 70%
“…Although the increase of nickel hydroxide depended on the holding time in the bath, the peak position of nickel oxide (854.5 eV) was barely observed. 13) Furthermore, the Ni 2p peak was hardly observed for the surface of the device, and a small nickel peak was observed in the layer for the device kept in the bath. This result suggests that magnesium oxide is present predominantly near the surface, as shown in Fig.…”
Section: Surface State Analysis By Xpsmentioning
confidence: 98%
“…13) When the device was kept in the bath, the hydroxide state of nickel (856.6 eV) gradually appeared in the layer. 13) The layer consisted of a mixture of metallic nickel and nickel hydroxide, as shown in Fig. 7(d).…”
Section: Surface State Analysis By Xpsmentioning
confidence: 99%
“…30,31 For sputter depth profiling, Ar ions of 4 keV and a scan size of 2 mm × 2 mm were performed. As Oswald and Bruckner 30 illustrated, these conditions could result in a typical sputter rate of 3-5 nm min − 1 in as-prepared CdX nanosheet films.…”
Section: Xps Depth Profile Analysismentioning
confidence: 99%
“…30,31 For sputter depth profiling, Ar ions of 4 keV and a scan size of 2 mm × 2 mm were performed. As Oswald and Bruckner 30 illustrated, these conditions could result in a typical sputter rate of 3-5 nm min − 1 in as-prepared CdX nanosheet films. As shown in Figures 5a and b, the atomic concentrations of Cd, S and Ag are maintained at the approximate ratio of~55.4: 43.1: 1.5 in the CdS Oriented attachment of nanoparticles H Qian et al nanosheet film as the sputtering proceeds into the film.…”
Section: Xps Depth Profile Analysismentioning
confidence: 99%